Ecomaterialism in scenography. Issue 1 (2nd April 2016) - Beer, Tanja
ABSTRACT: Contemporary ecological concerns bring with them an opportunity for innovation; to rethink traditional practices and forge ecologically inspired approaches that push intellectual and creative boundaries. This article investigates contemporary notions of ecology and materialism ('ecomaterialism'), which abandon traditional disciplinary divides and seek to unify the human self with the broader system of ecological organisation. Using a practice-based research example ( Strung ), I examine the potential for ecomaterialism to lead to new modes of practice in scenography, where expanded ideas of material entanglement, across bodies, ecosystems and built environments, are central to sustainability in performance design.